Can AI Detect Bone Fractures More Accurately Than Physicians? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Artificial intelligence (AI) is rapidly transforming various sectors, and healthcare is no exception. One of the most promising applications of AI in medical...
Keywords: AI in Medical Imaging and Diagnostics; Detect; Fractures; Accurately; Artificial Intelligence; Deep Learning; Healthcare